2019
DOI: 10.1111/myc.12909
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal combinations in Mucorales: A microbiological perspective

Abstract: Summary Mucormycosis mostly affects immunocompromised patients and is associated with a high morbidity and mortality despite currently available treatments. In that context, combination therapy might be the key to a better outcome for these patients. Purpose of this review is to summarise and to discuss the current combination data obtained in vitro, in vivo in animal models of mucormycosis, and in patients. In vitro combination studies showed that most of the interactions between antifungal drugs were indiffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 133 publications
0
29
0
Order By: Relevance
“…Already prior to the COVID-19 pandemic repurposing of drugs had become trendy. Repurposed drugs have shown activity against bacteria 29 , yeasts 29,30 , and filamentous fungi [31][32][33][34] . Colistin is a drug of last resort with activity against multidrug-resistant gram-negative bacteria such as Pseudomonas aeruginosa, Klebsiella pneumoniae, or Acinetobacter baumanii 35 ; but colistin has also shown to damage the cell membrane of C. albicans 17 , which could make it an interesting partner in combination therapy against multidrug-resistant C. auris infections.…”
Section: Discussionmentioning
confidence: 99%
“…Already prior to the COVID-19 pandemic repurposing of drugs had become trendy. Repurposed drugs have shown activity against bacteria 29 , yeasts 29,30 , and filamentous fungi [31][32][33][34] . Colistin is a drug of last resort with activity against multidrug-resistant gram-negative bacteria such as Pseudomonas aeruginosa, Klebsiella pneumoniae, or Acinetobacter baumanii 35 ; but colistin has also shown to damage the cell membrane of C. albicans 17 , which could make it an interesting partner in combination therapy against multidrug-resistant C. auris infections.…”
Section: Discussionmentioning
confidence: 99%
“…The combinations in these studies were isavuconazole with amphotericin and isavuconazole with micafungin. All other in vitro studies showed either synergy or indifference 26…”
Section: Discussionmentioning
confidence: 87%
“…In vitro synergy between antifungals and immune suppressive drugs has been found for yeasts [30][31][32][33][34][35][36], and filamentous fungi such as the Mucorales [24,25,37,38], and Aspergillus species [39,40]. Nevertheless, in vitro indifference [21,41] and even antagonism has been reported for the combinations of voriconazole with tacrolimus or cyclosporin A against four A. fumigatus isolates and one A. fumigatus isolate, respectively [41].…”
Section: Discussionmentioning
confidence: 99%